Tipping points and regime shifts in reindeer husbandry: A systems approach - Löf, Annette (2022)
This chapter addresses the challenges to reindeer husbandry in Fennoscandia from a systems perspective. Drawing on information in other chapters in this book, the specific focus is on so called tipping points, or abrupt changes in the coupled social-ecological system. Tipping points may occur when external drivers push a system to an alternative system state, characterized by different feedbacks than in the original state. Compared to ‘ideal’ or traditional reindeer husbandry, examples of alternative states include reliance on supplementary feeding to compensate for losses of pastures, fencing herds to provide protection from predation, becoming a meat-processing industry based on more centralized herding practices and a total loss of reindeer husbandry. All of these states are seen as undesirable by the herders. Reindeer husbandry, as it is currently practised, requires intact social-ecological relationships within the herding districts, as well as in their interaction with the external society. These system qualities need to be strengthened as they innately provide resilience, and will demand structural, institutional and legislative changes, but also discursive changes of how we imagine what sustainability is, and whether herders are treated as one of many stakeholders or as the rights holders that they really are according to the law.